Analysis of Creativity and Critical Thinking Skills Through Project-Based Learning of Smart Solar Panel System - Prastyaningrum, Ihtiari; Ardi, Pramudya; Wahyudi, Wahyudi (Yayasan Indonesia Emerging Literacy Education, 2024)
The challenges of today's world of work are very complex. Not only abilities based on grades on paper but other supporting abilities must also be possessed by graduates. In this era, graduates are expected to have other skills to support their academic abilities. These skills are known as 21st-century skills. This research aims to determine the level of creativity and critical thinking of students in the sixth semester of the Electrical Engineering Education Study Program. Analysis of these two skills is carried out through project-based learning, taking the project focus on smart solar panels. The selection of research focus is based on bibliometric analysis, where in the last 10 years, research related to project-based learning on renewable energy for creativity analysis and critical thinking still needs to be carried out. The research method used in this research is descriptive research with a qualitative and quantitative approach. The data collection process was carried out through direct observation in the field and also through assessment sheets by colleagues and lecturers. Based on the results of data processing, results were obtained which showed that project-based learning was suitable for analyzing critical thinking skills and also honing creativity.